2020
DOI: 10.1002/mnfr.202000505
|View full text |Cite
|
Sign up to set email alerts
|

Tea Drinking Alleviates Diabetic Symptoms via Upregulating Renal Water Reabsorption Proteins and Downregulating Renal Gluconeogenic Enzymes in db/db Mice

Abstract: Scope: Tea, made from the plant Camellia sinensis, is known to have anti‐diabetes effects and different mechanisms of action are proposed. Kidney is a vital organ in managing water reabsorption and glucose metabolism, and is greatly influenced by diabetes. The present study investigates the effects of tea administration on water reabsorption and gluconeogenesis in the kidney of diabetic mice. Methods and results: Db/db mice are given tea infusion as drinking fluid when they begin to exhibit hyperglycemia. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Now it is a popular beverage worldwide, especially in adults starting to focus on health concerns, because it does not have significant caloric content and yet possibly possesses multiple health-promoting effects, such as body weight control, metabolic syndrome alleviation, prevention of cancer, diabetes mellitus, and cardiovascular, neurodegenerative or infective diseases ( Yang et al, 2002 ; Yang et al, 2016 ; Zhang et al, 2019 ; Z. Zhang et al, 2021 , Zhang et al, 2021 ; Zhao et al, 2020 ). Some green teas contain unusually high quantities of catechins (up to 35% of dry weight pending on the cultivar) including epicatechin, epicatechin gallate, epigallocatechin, and EGCG ( Datta et al, 2022 ; Yang et al, 2002 ).…”
Section: Antiviral Activity Of Egcg Against Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Now it is a popular beverage worldwide, especially in adults starting to focus on health concerns, because it does not have significant caloric content and yet possibly possesses multiple health-promoting effects, such as body weight control, metabolic syndrome alleviation, prevention of cancer, diabetes mellitus, and cardiovascular, neurodegenerative or infective diseases ( Yang et al, 2002 ; Yang et al, 2016 ; Zhang et al, 2019 ; Z. Zhang et al, 2021 , Zhang et al, 2021 ; Zhao et al, 2020 ). Some green teas contain unusually high quantities of catechins (up to 35% of dry weight pending on the cultivar) including epicatechin, epicatechin gallate, epigallocatechin, and EGCG ( Datta et al, 2022 ; Yang et al, 2002 ).…”
Section: Antiviral Activity Of Egcg Against Sars-cov-2mentioning
confidence: 99%
“…Some green teas contain unusually high quantities of catechins (up to 35% of dry weight pending on the cultivar) including epicatechin, epicatechin gallate, epigallocatechin, and EGCG ( Datta et al, 2022 ; Yang et al, 2002 ). Among these, EGCG is the most abundant (over 50% in most cases) ( Yang et al, 2002 ; Zhao et al, 2020 ) and is the best-documented in terms of antioxidant and prooxidant activities as well as its redox-associated biological functions ( Datta et al, 2022 ; Dong et al, 2016 ; Yang & Hong, 2013 ).…”
Section: Antiviral Activity Of Egcg Against Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence demonstrates that EGCG is helpful in controlling blood glucose in diabetic subjects ( Chen et al, 2009 ; Kao, Chang, Lee, & Chen, 2006 ; Sae-tan, Grove, & Lambert, 2011 ; Wolfram et al, 2006 ; Yang, Zhang, Zhang, Huang, & Wang, 2016 ; Zhao, Wu, Wang, Yang, & Zhang, 2020 ). Moreover, several studies in animal models and humans have shown that EGCG suppresses RAGE signaling pathway; specifically, 1) treatment with EGCG (10 mg/kg and 50 mg/kg, i.p.)…”
Section: Reduction Of Covid-19 Diabetes Comorbidity Risk By Egcgmentioning
confidence: 99%
“…The possible mechanisms of actions of tea preparations in mitigating metabolic diseases have been studied extensively. These include a decrease in micronutrient absorption, promotion of catabolism by EGCG through metabolic regulators such as AMP-activated protein kinase (AMPK), enhancement of thermogenesis and increase in renal water reabsorption [ 8 , 11 , 12 , 13 , 14 ]. The beneficial health effects of green tea polyphenols and EGCG have also been suggested to be mediated through their modulation of gut microbiota [ 15 ].…”
Section: Introductionmentioning
confidence: 99%